Identification key for drosophilid species (Diptera, Drosophilidae) exotic to the Neotropical Region and occurring in Brazil - Yuzuki,Keven (2020)
Abstract Thirteen species of drosophilid exotic to the Neotropical Region are recorded in Brazil, and some of them are highly invasive and threaten significantly fruit cultures. We provide an illustrated key for identifying these species, and briefly discuss their taxonomic status, distribution, and occurrence in the Neotropics. The key should not only support newcomers to the study of Drosophila but also facilitate their identification by those interested in insects associated with cultivated areas.